2006
DOI: 10.1186/1747-1028-1-20
|View full text |Cite
|
Sign up to set email alerts
|

FAT 10, a gene up-regulated in various cancers, is cell-cycle regulated

Abstract: BackgroundFAT10 is a member of the ubiquitin-like-modifier family of proteins. Over-expression of the FAT10 gene was observed in the tumors of several epithelial cancers. High FAT10 expression was found to lead to increased chromosome instability via the reduction in the kinetochore localization of MAD2 during the prometaphase stage of the cell-cycle. FAT10 expression was also previously reported to be regulated by cytokines and p53.ResultsHere, we report that FAT10 expression is regulated at the protein and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 23 publications
(33 reference statements)
1
30
0
Order By: Relevance
“…The observation that FAT10 modifies p53 and stimulates its transcriptional activity is in agreement with the potential roles of FAT10 in the regulation of cell-cycle, apoptosis, proliferation arrest, and tumorigenesis [5, 7, 8]. The consequence of p53 stimulation is defined by ‘cellular context’ or particular cell genotype [26].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The observation that FAT10 modifies p53 and stimulates its transcriptional activity is in agreement with the potential roles of FAT10 in the regulation of cell-cycle, apoptosis, proliferation arrest, and tumorigenesis [5, 7, 8]. The consequence of p53 stimulation is defined by ‘cellular context’ or particular cell genotype [26].…”
Section: Discussionsupporting
confidence: 61%
“…FAT10 is originally identified as a gene encoded in the major histocompatibility complex class I locus and is inducible with TNF-α and interferon-γ [4]. It is regulated in a cell-cycle dependent fashion with the highest expression at the S phase [5], and is negatively regulated by p53 [6]. Although the functions of FAT10 are unclear, it has been implicated to play important roles in many cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…FAT10 is overexpressed in numerous types of malignancies, including HCC, colorectal tumors, gastric tumors and gynecological tumors ( 8 , 9 , 29 ). Previous studies have suggested that FAT10 has a pathological role in cancer via involvement in mechanisms other than its proteasome targeting function ( 29 ). However, the role of FAT10 in tumorigenesis remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…FAT10 expression is induced by interferon (IFN)-γ and tumor necrosis factor α (TNFα) (Lukasiak et al , 2008; Oliva et al , 2010). Increased FAT10 gene expression and protein levels have been observed in various cancers (Raasi et al , 2001; Lee et al , 2003; Lim et al , 2006; Qing et al , 2011), and interference of FAT10 could suppress cell proliferation by inhibiting the cell cycle S-phase entry and inducing apoptosis (Chen et al , 2014). Despite these reports, the biological significance of the FAT10 system in liver tumor development remains unclear and warrants further research.…”
Section: Introductionmentioning
confidence: 99%